Pengaruh Teman Sebaya, Self control, dan Literasi Keuangan Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Penerima Beasiswa Bank Indonesia Solo - Carmelita Devina Cristy; Fadjar Harimurti (Pusat Riset dan Inovasi Nasional, 2026)
This study investigated the influence of peers, self-control, and financial literacy on the personal financial management of Bank Indonesia (GenBI) scholarship recipients in Solo. A comprehensive quantitative survey was conducted, in which all 300 scholarship recipients participated. Primary data were collected via questionnaires and analyzed using multiple linear regression. The analysis revealed a positive and significant influence on personal financial management. Of the three factors, self-control made the largest contribution. Simultaneously, the research model was able to explain 39.7% of the variance in the students' financial management. These results confirm that financial behavior is determined not only by financial literacy but also by psychological factors as well as social and environmental influences